(untitled) (The Conference Hub, 2025)
The article highlights the role of extracurricular activities in developing functional literacy among primary school students. The psychopedagogical importance of library work, creative notebooks, media and digital literacy activities, as well as cooperation with family and community, is analyzed. Based on UNESCO, OECD, and IEA reports and Uzbekistan’s educational policies, the paper demonstrates ways to foster independent thinking, creativity, and critical analysis skills through extracurricular activities.